2018
DOI: 10.20965/ijat.2018.p0413
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Straight Fibers Pneumatic Muscle

Abstract: This paper presents the development and implementation of a pneumatic muscle actuator based on an idea proposed by a research group at the University of Warsaw. The muscle comprises a silicone rubber tube with plugs at the ends. The tube wall contains high-rigidity wires arranged parallel to the tube axis. Circular rings are present on the exterior of the tube. When air is introduced into the tube, the actuator becomes bulky and contracts. In order to establish a prediction model of muscle behavior, a finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The former have been the subject of research activities and find space in some industrial applications, as they are available in the automation components market; the latter are not present in the market but are often designed ad hoc and integrated into commonly used devices such as blood pressure measurement systems and other medical devices, such as car seats and massage chairs. Two types of pneumatic muscles have been developed [11, 12]: straight fibres and braided, also known as McKibben muscle. The straight fibres pneumatic muscle (Figure 5(a)) is made of a silicone cylindrical chamber in the wall in which a cage consists of 40 Kevlar threads, arranged longitudinally and held in position by two end rings, in which one is buried inside the silicone and the other is connected to the head that contains the air supply/discharge pipe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former have been the subject of research activities and find space in some industrial applications, as they are available in the automation components market; the latter are not present in the market but are often designed ad hoc and integrated into commonly used devices such as blood pressure measurement systems and other medical devices, such as car seats and massage chairs. Two types of pneumatic muscles have been developed [11, 12]: straight fibres and braided, also known as McKibben muscle. The straight fibres pneumatic muscle (Figure 5(a)) is made of a silicone cylindrical chamber in the wall in which a cage consists of 40 Kevlar threads, arranged longitudinally and held in position by two end rings, in which one is buried inside the silicone and the other is connected to the head that contains the air supply/discharge pipe.…”
Section: Resultsmentioning
confidence: 99%
“…In Figures 2(a)–2(c), an example of numerical results of an isotonic test simulation, based on the model proposed, is shown. A research work was also carried out for straight fibres pneumatic muscles [12], and in Figure 2(d), an example of a characteristic graph obtained with the design curve is shown together with the curve required by the designer (traction force F vs. shortening Δ L ) for a biomedical application.…”
Section: Methodsmentioning
confidence: 99%
“…27 Similarly, straight fiber PAMs use an elastic tube featuring reinforced fibers to increase membrane strength, and they form a spherical shape when actuated. [28][29][30][31] Other soft pneumatic actuators (SPAs) apply this concept of using a stiff embedded sheet on the inside of soft elastomer 32 or creating a three-dimensional (3D)-printed soft contractile actuator consisting of stiff and soft composites. 33 These PAMs use an elastic material as the actuator's membrane, which stretches and expands under high applied pressure, and use a stiffer material to limit membrane expansion, resulting in a pre-determined shape and contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and a lot of application can be countered about the MKMs: theoretical and numerical models were defined [19][20][21] as well as applications of them for rehabilitation, robotics and wearable devices [22][23][24][25][26][27][28]. On the contrary, few studies can be found in literature about SFMs which first presented in 1970 [29,30]: some studies were focused on the comparison between SFMs and MKMs [31][32][33], on the development of a validated numerical model of them [34] and a robotic application in the field of the human rehabilitation [1,35].…”
Section: Introductionmentioning
confidence: 99%